Comparative carbon emission assessments of recycled and natural aggregate concrete: Environmental influence of cement content - Sabau, Marian (2021)
This work examines the environmental and geochemical impact of recycled aggregate concrete production with properties representative for structural applications. The environmental influence of cement content, aggregate production, transportation, and waste landfilling is analysed by undertaking a life cycle assessment and considering a life cycle inventory largely specific for the region. To obtain a detailed insight into the optimum life cycle parameters, a sensitivity study is carried out in which supplementary cementitious materials, different values of natural-to-recycled aggregate content ratio and case-specific transportation distances were considered. The results show that carbon emissions were between 323 and 332 kgCO2e per cubic metre of cement only natural aggregate concrete. These values can be reduced by up to 17% by replacing 25% of the cement with fly ash. By contrast, carbon emissions can increase when natural coarse aggregates are replaced by recycled aggregates in proportions of 50% and 100%, and transportation is not included in analysis. However, the concrete with 50% recycled aggregate presented lower increase, only 0.3% and 3.4% for normal and high strength concrete, respectively. In some cases, the relative contribution of transportation to the total carbon emissions increased when cement was replaced by fly ash in proportions of 25%, and case-specific transportation distances were considered. In absolute values, the concrete mixes with 100% recycled aggregates and 25% fly ash had lower carbon emissions than concrete with cement and natural aggregates only. Higher environmental benefits can be obtained when the transportation distances of fly ash are relatively short (15–25 km) and the cement replacement by fly ash is equal or higher than 25%, considering that the mechanical properties are adequate for practical application. The observations from this paper show that recycled aggregate concrete with strength characteristics representative for structural members can have lower carbon emissions than conventional concrete, recommending them as an alternative to achieving global sustainability standards in construction.